Contagious itch in humans: a study of visual 'transmission' of itch in atopic dermatitis and healthy subjects - Papoiu, A.D.P.; Wang, H.; Coghill, R.C.; Chan, Y-H.; Yosipovitch, G. (British journal of dermatology (1951), 2011)
Summary Background  Anecdotal evidence suggests that ‘contagious’ itch occurs in daily life when we see other people itch and scratch. This phenomenon has not previously been studied systematically, and factors which can amplify itch perception were unknown. Objectives  We investigated whether exposure to visual cues of itch can induce or intensify itch in healthy subjects and patients with atopic dermatitis (AD). Methods  Participants received histamine or a saline control delivered to the forearm and were asked to watch short video clips of people scratching. Spontaneous scratching induced by visual cues was monitored and analysed. Results  Patients with AD reported a higher itch intensity and scratched more frequently while watching itch videos, even in the presence of mock itch stimuli. Conclusions  Human susceptibility to develop itch when exposed to visual cues is confirmed; it appears to be amplified in patients with AD. These findings suggest that interpersonal social cues can dramatically alter the subjective sensory experience of itch.